Adopting New Heritage Model for Ecotourism Plan in National Key Economic Areas to Improve Tourism Sector Performance in Malaysia - ABD RASHID, Intan Maizura; ABU SAMAH, Irza Hanie; WAN HUSAIN, Wan Ahmad Fauzi; MANSOR, Mohd Fitri; HASSAN, Sallahuddin (Journal of Environmental Management and Tourism; Vol 11 No 1 (2020): JEMT Volume XI Issue 1(41) Spring 2020DO - 10.14505//jemt.v11.1(41).19, 2020)
Tourism sector performance contributes to a large part of the Malaysian service economy (The World Factbook 2013). In 2016, Malaysia has faced an economic crisis and it affects tourism sectors. Moreover, data from the Ministry of Tourism have shown that the number of tourists is decreasing at 1.5% in March 2016. This scenario has become a serious issue for government because Tourism Sector is one of the government’s important agenda in the National Key Economic Areas (NKEA) through National Ecotourism Plan. According to the Ministry of Tourism (MoT 2013), the nation's tourism sector is now the sixth largest contributor to the national economy in 2014. Unfortunately, among of all agendas in 21 Action Plans, none of it mentions about heritage tourism. The study was done among the tourist at several heritage site in Malaysia and 200 questionnaires, were distributed. Correlation analysis and regression analysis were perform, thus the result indicates that Heritage Spending Behavior (r=0.55, p=0.001,) shows the highest of positive significant result toward Tourism Industrial Performance compared with other two variables. Lastly, it will guide the government by understanding the important need of visitors and it can apply to other heritages sites in Malaysia.